Impact of European Market Infrastructure Regulation on Financial Markets - Hoffmann, Petr; Baran, Jaroslav; Burešová, Jana; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2013)
The aim of this bachelor thesis is to take a closer look on the European Market Infrastructure Regulation (EMIR) which was adopted and entered into force on 16th August 2012. The thesis examines the European Commission proposal and the final form of a regulation on OTC derivatives, central counterparties and trade repositories, which has been adopted in the light of a G-20 commitment expressed in 2009. The main purpose is to introduce and to assess this new financial legislation that is about to regulate OTC markets. One of the most important parts is a comparison of American and European legislation in terms of this financial regulation. The outcome of this thesis is a critical evaluation of possible impacts of EMIR on financial markets and on end-users.
Vedoucí práce: Jaroslav Baran
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: bankovnictví a pojišťovnictví [obor bakal. práce]; bakalářské práce; bachelor's theses